(untitled) (Studia theodisca, 2011)
This article focuses on rhetorical handbooks written in Germany during the 19th century. It traces back the tradition of rhetorical handbooks, which started in ancient Greece and developed into a branch of literature in Europe, where it is attested in various languages of the young national states. The books written and edited during the 19th century contribute to the history of rhetoric in Europe and demonstrate how rhetoric was implemented into the German educational system of the 19th century. A list of handbooks published during this period is a complementary element of research presented in this article.